2020
DOI: 10.1186/s12906-020-02925-4
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the mechanism of the effects of Paeoniae Radix Alba on iron-deficiency anaemia through a network pharmacology-based strategy

Abstract: Background: Paeoniae Radix Alba, the root of the plant Paeonia lactiflora Pall, is a common blood-enriching drug in traditional Chinese medicine. Its effectiveness in the clinical treatment of anaemia is remarkable, but its potential pharmacologic mechanism has not been clarified. Methods: In this study, the potential pharmacologic mechanism of Paeoniae Radix Alba in the treatment of iron-deficiency anaemia was preliminarily elucidated through systematic and comprehensive network pharmacology. Results: Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 106 publications
0
21
0
Order By: Relevance
“…In general, molecules with “Oral bioavailability”(OB) ≥ 30% and “Drug likeness”(DL) ≥ 0.18 are considered to have better pharmacological effects, therefore this standard is also often used when screening for the active ingredients of drugs ( Alam et al., 2015 ; Li Z. et al., 2020 ; Meng et al., 2020 ; Ye et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, molecules with “Oral bioavailability”(OB) ≥ 30% and “Drug likeness”(DL) ≥ 0.18 are considered to have better pharmacological effects, therefore this standard is also often used when screening for the active ingredients of drugs ( Alam et al., 2015 ; Li Z. et al., 2020 ; Meng et al., 2020 ; Ye et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…used when screening for the active ingredients of drugs (Alam et al, 2015;Li Z. et al, 2020;Meng et al, 2020;Ye et al, 2020).…”
Section: Screening Active Ingredients In Pgmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly used for blood deficiency, irregular menstruation, spontaneous sweating, night sweats, flank pain, abdominal pain, limb pain, headache, and dizziness. 6,7 Previous studies showed that PRA could be used for anti-inflammatory effects, 8 immune regulation, 9 treatment of depression 10,11 and anemia, 12 promotion of peripheral nerve regeneration, 13 and treatment of viral infections. 14 Modern studies of pharmacological mechanisms have found that the main active components of PRA include paeoniflorin, paeonol, paeonin, benzoylpaeoniflorin, albiflorin, oxypaeoniflorin, paeoniflorigenone, benzoic acid, β-sitosterol, and gal-lotannin.…”
Section: Pharmacological Studies On the Active Ingredients Of The Sixmentioning
confidence: 99%
“…Simultaneously, the top 10 core targets interacting with ACE2 were found through the STRING database. 16…”
Section: Construction Of Protein-protein Interactions Networkmentioning
confidence: 99%